2009
DOI: 10.1111/j.1365-2699.2009.02197.x
|View full text |Cite
|
Sign up to set email alerts
|

A weak upward elevational shift in the distributions of breeding birds in the Italian Alps

Abstract: Numerous studies have demonstrated the impact of recent climate warming on the distributions of specific groups of plants (Grabherr et al. ABSTRACTAim To test whether bird assemblages are shifting upwards in their elevational distribution in synchrony with current climate warming and/or habitat changes.Location A gradient of elevation in the Italian Alps (Alta Valsessera, Piedmont).Methods We used data from two recent atlas surveys performed on a 1 · 1 km grid at an 11-year interval (1992-94 and 2003-05). We m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 62 publications
(110 reference statements)
5
73
0
Order By: Relevance
“…160 m/°C; Hughes 2000). Here, our modelling results coincide with the empirical study of Popy et al (2010) who detected a shift in elevation of bird species in the Italian Alps of 29.4 m/C°. The results are also backed by findings of Randin et al (2009) as well as Luoto and Heikkinen (2008) who stated that environmental heterogeneity may significantly buffer the impact of climate change on species distribution.…”
Section: Response To Climate Changesupporting
confidence: 92%
See 1 more Smart Citation
“…160 m/°C; Hughes 2000). Here, our modelling results coincide with the empirical study of Popy et al (2010) who detected a shift in elevation of bird species in the Italian Alps of 29.4 m/C°. The results are also backed by findings of Randin et al (2009) as well as Luoto and Heikkinen (2008) who stated that environmental heterogeneity may significantly buffer the impact of climate change on species distribution.…”
Section: Response To Climate Changesupporting
confidence: 92%
“…1). This is especially the case if the species under study relies on patchily distributed habitat and inhabits steep terrain as do Rock Ptarmigan (Rahbek 2005;Popy et al 2010). It clearly demonstrates how invaluable small-scale atlas data can be to accurately model the species distribution and its range shifts.…”
Section: Rock Ptarmigan's Habitat Requirements: a Matter Of Scalementioning
confidence: 94%
“…Many studies have already provided substantial evidence of the effect of climate change on geographic range, migration, breeding phenology and demographic factors such as breeding performance and survival (Crick 2004;PearceHiggins and Green 2014). Specifically, there is now compelling evidence that the distribution range of some bird species has shifted northward in the northern hemisphere (Thomas and Lennon 1999;Jiguet et al 2006) or to higher altitudes (Shoo et al 2006;Pounds et al 1999), although the results concerning elevational shifts of upland and alpine birds appear somewhat variable (Archaux 2004;Popy et al 2010;Maggini et al 2011).…”
Section: Introductionmentioning
confidence: 96%
“…The shift pattern for these species is of type F according to our catalogue, i.e., mainly a retraction from low elevations. In their assessment in an alpine valley in Italy, Popy et al (2009) found that the mean elevations increased for the majority of species over the considered period of 11 years, but that the average change was not significantly different from zero. However, a significant upward shift of 29 m of the bird zonation could be identified.…”
Section: Shifts In the Elevational Distribution Of Breeding Birds In mentioning
confidence: 99%